Perkembangan Pengelolaan Arsip Elektronik Di Indonesia: Tinjauan Pustaka Sistematis - Fajar Nyfantoro; Tamara Adriani Salim; Anon Mirmani (Program Studi Kearsipan, DBSMB SV UGM, 2019)
Introduction. In Indonesia, technology has developed in various fields, this study explores the management of archives in Indonesian institutions still uses conventional archives or manages records electronically. The result of our findings also convey information on the development of electronic records management that has been carried out through a systematic literature review.Methods. A systematic literature review method was used for exploring electronic records management study. The use of this method is designed to search for, assess, and synthesize the best available evidence. The goal is to get informative, evidence-based answers related to the research questions.Analysis. The research will be analyzed based on the theory of Population, Intervention, Comparison, Outcomes and Context (PICOC). Results and Discussion. Carried out through a systematic literature review method, our results found 20 documents that had links with electronic archive management activities. The institution applies electronic archive management by using software technology such as computer-based applications, Android-based applications on mobile phones, and website-based network applications to various processes of archiving activities.Conclusion Our results suggest that the management of institutional records in Indonesia should follow the development by implementing electronic management.